LITERASI FISIK DAN SPORTMANSHIP GURU PJOK: ANALISIS KOMPARATIF BERDASARKAN JENJANG SEKOLAH DI KABUPATEN PASURUAN - Hidayati, Nila; Aswara, Agung Yuda; Sucipto, Adi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The increasing prevalence of sedentary lifestyles among children and adolescents highlights the strategic role of Physical Education, Sports, and Health (PESH) teachers in promoting active lifestyles and character development through sports. In this context, physical literacy and sportmanship are considered key indicators of PESH teacher professionalism. However, there remains an ongoing debate regarding whether these professional characteristics are shaped by differences in school levels or develop relatively uniformly through the culture of the teaching profession and sport. This study aimed to analyze differences in physical literacy and sportmanship among PESH teachers across school levels in Pasuruan Regency, Indonesia. A quantitative approach with a comparative ex post facto design was employed. The sample consisted of 152 PESH teachers, including 106 elementary school teachers, 28 junior secondary school teachers, and 18 senior secondary school teachers, selected through proportional random sampling. Data were collected using questionnaires and analyzed through descriptive statistics and One-Way Analysis of Variance (ANOVA). The results revealed no significant differences in physical literacy (F = 0.235, p = 0.791) or sportmanship (F = 1.362, p = 0.259) across school levels. These findings indicate that PESH teachers at elementary, junior secondary, and senior secondary levels demonstrate relatively comparable levels of physical literacy and sportmanship. This study contributes to the field of physical education by providing empirical evidence that school level is not a primary differentiating factor in explaining variations in teachers’ physical literacy and sportmanship. ABSTRAK Meningkatnya gaya hidup sedentari pada anak dan remaja menempatkan guru Pendidikan Jasmani, Olahraga, dan Kesehatan (PJOK) sebagai aktor penting dalam membangun budaya hidup aktif dan pendidikan karakter melalui olahraga. Dalam konteks tersebut, literasi fisik dan sportmanship menjadi dua indikator utama profesionalitas guru PJOK. Namun, masih terdapat perdebatan mengenai apakah karakteristik profesional tersebut dipengaruhi oleh perbedaan jenjang sekolah atau berkembang secara relatif seragam melalui kultur profesi olahraga. Penelitian ini bertujuan menganalisis perbedaan literasi fisik dan sportmanship guru PJOK berdasarkan jenjang sekolah di Kabupaten Pasuruan. Penelitian menggunakan pendekatan kuantitatif dengan desain komparatif ex post facto. Sampel penelitian berjumlah 152 guru PJOK yang terdiri atas 106 guru SD, 28 guru SMP, dan 18 guru SMA yang dipilih menggunakan teknik proportional random sampling. Data dikumpulkan menggunakan kuesioner dan dianalisis melalui statistik deskriptif serta One-Way Analysis of Variance (ANOVA). Hasil penelitian menunjukkan bahwa tidak terdapat perbedaan yang signifikan pada literasi fisik (F = 0,235; p = 0,791) maupun sportmanship (F = 1,362; p = 0,259) berdasarkan jenjang sekolah. Temuan ini menunjukkan bahwa guru PJOK pada jenjang SD, SMP, dan SMA memiliki tingkat literasi fisik dan sportmanship yang relatif setara. Penelitian ini berkontribusi pada kajian pendidikan jasmani dengan memberikan bukti empiris bahwa jenjang sekolah belum dapat diposisikan sebagai faktor pembeda utama dalam menjelaskan variasi literasi fisik dan sportmanship guru PJOK.